A 2‐year Choral Singing intervention with community‐dwelling older adults at risk of cognitive decline to improve bio‐psychological outcomes: An open‐label Randomized Controlled Trial. (20th December 2022) - Ng, Ted K.S.; Mahendran, Rathi; Kua, Ee‐Heok; Feng, Lei
Abstract: Background: Few randomized controlled trials (RCTs) have investigated the effects of choral singing (CS) on community‐dwelling older adults at‐risk of cognitive decline. Specifically, scarce literature exists on the effects of CS on affective symptoms and other bio‐psychological risk factors of cognitive decline, including low‐grade inflammation and perceived stress. Extant interventional studies on CS lack robust RCT design incorporating an active control arm controlling for active components which are not intervention‐specific. Addressing these gaps in knowledge, we initiated the CS‐RCT and hypothesized that a 2‐year CS intervention with older adults at risk of cognitive decline will improve affective, i.e., depressive and anxiety, symptoms, high‐sensitivity c‐reactive protein (hs‐CRP) levels, and perceived stress. Method: Conducting a parallel‐arm and open‐label RCT, we recruited 93 community‐dwelling older adults at‐risk of cognitive decline, i.e., self‐reported cognitive complaints, cognitive impairment based on neuropsychological test scores or had multiple medical risk factors of dementia. They were randomized into either the treatment arm, CS, or the active control arm, the health education program (HEP) matched with non‐intervention‐specific components. Both the CS and HEP arms involved weekly 1‐hour group sessions held continuously for two years in parallel. In this paper, we examined the a priori registered (ClinicalTrials.gov Identifier: NCT02919748) secondary outcomes of the RCT at baseline, 1‐year, and 2‐year time‐points. The outcomes were depressive and anxiety symptoms, hs‐CRP levels, and perceived stress, using the Geriatric Depression Scale‐15 (GDS‐15), Geriatric Anxiety Inventory‐20 (GAI‐20), commercial plasma hs‐CRP ELISA kit, and the perceived stress scale (PSS), correspondingly. Linear‐mixed models were used to examine the effect of CS on all measures using intention‐to‐treat. Benjamini‐Hochberg procedure was used to correct for multiple testing. Result: Compared to the HEP arm, CS participants experienced no significantly modified scores on GDS‐15, GAI‐20, plasma hs‐CRP levels, and PSS throughout the 2‐year intervention time‐points. Conclusion: In contrary to previous studies using passive controls, compared to HEP as an active comparator, CS did not improve affective symptoms and two other bio‐psychological risk factors of cognitive decline in at‐risk community‐dwelling older adults. Our findings highlight the critical importance of examining real‐world‐efficacy of a nonpharmacological intervention among a community‐based sample (Stage 3).